Keputihan Pada Wanita Usia Subur Menggunakan Ekstrak Daun Sirsak - Suwanti Suwanti; Yonferizal MR Koto (Poltekkes Kemenkes Surakarta, 2016)
Abstract: The leaves of the soursop, woman of fertile age, Whitish. Whitish is the complaint most often found in women. Cause of vaginal discharge is a matter of cleanliness around the sex organs, such as less clean when dry the sex organs after urination and defecation. Soursop leaf oil contains asitrin, sineol 50% -65%, a- pinene, limonene and dipenten, mngandung asetogini compounds, among others asimisin, bulatasin and skuamosin. Peneitian goal is to determine the effectiveness of the use of soursop leaves against vaginal discharge in women of childbearing age. The research design was quasi experiment with pretest posttes approach, where the study was conducted grouping members of the experimental group. The subjects of this study were women of childbearing age who experience vaginal discharge by 30 samples. The statistical test used in this study is the Mann Whitney U Test. The results showed that women of childbearing age who experience vaginal discharge cured after taking the leaf extract of soursop 23 people (76.7%).